Production of xylonic acid from xylose using recombinant E. Coli bl21 (DE3): effect of medium requirement - Rafidah, Mohamed Ali Hanapiah (2022)
Xylonic acid (XA) is a valuable organic acid that has various applications similar to other sugar acids such as gluconic acid (GA). Xylonic acid can be used in food, pharmaceutical and chemical industries as it has similar characteristics as sugar acids. Some of the applications include the function as complexing agent or chelator, in dispersal of concrete and as precursor for compounds such as co-polyamides, hydrogels and 1,2,4-butanetriol. In this study, recombinant Escherichia coli (E.coli) BL21 (DE3) was used to produce xylonic acid by manipulating a few parameters such as growth medium; Luria Bertani (LB), Super Optimal Broth (SOB),Terrific Broth (TB), M9 Minimal Medium (M9), and 2×Yeast-Tryptone (2×YT), nitrogen sources (yeast and tryptone concentration), inducer of isopropyl ß-D-1-thiogalactopyranoside (IPTG) concentration (0.01, 0.05, 0.1, 0.5 and 1.0 mM), induction time (2, 3, 4, 5 and 6 h), substrate concentration as well as comparison of substrate from difference sources. Fermentation samples were analysed using hydroxamate method and DNS method to determine XA and xylose concentration from fermentation process at 24 h, 200 rpm and 37 °C. The recombinant E.coli BL21 (DE3) was exploited as an alternative to the existing producers, with the ability to enhance the conversion of xylose to xylonic acid, fast growth, easy to handle and robust. From the study, the best culture conditions for XA production in recombinant E.coli BL21 (DE3) was achieved in Super Optimal Broth (SOB) medium, 20 g/L of tryptone, 5 g/L of yeast extract, 0.5 mM of IPTG with 2 h induction time and 10 g/L of D-xylose as substrate. Concentration of XA as high as 8.69 g/L from 10 g/L xylose was obtained when fermentation was governed under the best culture conditions when comparing with oil palm frond (OPF) hydrolysate. The result during the fermentation of OPF hydrolysate shows low concentration of XA. This is due to the limitation of xylose efficiency metabolism which affected the growth rate of recombinant E. coli BL21 (DE3). These results suggest a promising industrial-scale production of XA from recombinant E. coli BL21 (DE3).